Electrospun Chitosan Functionalized with C12, C14 or C16 Tails for Blood-Contacting Medical Devices - Monica Dettin; Martina Roso; Grazia M. L. Messina; Giovanna Iucci; Valentina Peluso; Teresa Russo; Annj Zamuner; Marta Santi; Sabrina Milan Manani; Monica Zanella; Chiara Battocchio; Giovanni Marletta; et al. (Gels, 2022)
Medical applications stimulate the need for materials with broad potential. Chitosan, the partially deacetylated derivative of chitin, offers many interesting characteristics, such as biocompatibility and chemical derivatization possibility. In the present study, porous scaffolds composed of electrospun interwoven nanometric fibers are produced using chitosan or chitosan functionalized with aliphatic chains of twelve, fourteen or sixteen methylene groups. The scaffolds were thoroughly characterized by SEM and XPS. The length of the aliphatic tail influenced the physico-chemical and dynamic mechanical properties of the functionalized chitosan. The electrospun membranes revealed no interaction of Gram+ or Gram− bacteria, resulting in neither antibacterial nor bactericidal, but constitutively sterile. The electrospun scaffolds demonstrated the absence of cytotoxicity, inflammation response, and eryptosis. These results open the door to their application for blood purification devices, hemodialysis membranes, and vascular grafts.